The failure modes of different bedding slate under uniaxial compression - Shan-Li, Xie; Zhi-Quan, Huang; Peng, Cheng; Guang-Xiang, Yuan (Frontiers in Earth Science, 2026)
Slate, characterized by its layered structure, exhibits mechanical properties predominantly influenced by structural planes. To investigate the mechanical behavior and failure modes of slate under varying dip angles of structural planes, uniaxial compression tests were conducted on slate specimens. The study systematically examined the effects of dip angles on compressive strength, stress-strain curves, and failure patterns. Additionally, a particle flow model was established using PFC-2D to simulate the failure process of slate, with detailed analysis of stress responses under different dip angles. The results indicate that the compressive strength of slate exhibits significant anisotropy across different bedding inclinations. Overall, the strength distribution follows a “U-shaped” curve as the inclination angle varies. During uniaxial compression, the deformation process of slate specimens progresses through four distinct stages: compaction, elastic deformation, elastoplastic deformation, and failure. Three primary failure modes were identified: composite shear-tensile failure along bedding planes, shear failure along bedding planes, and compression-induced tensile failure involving both bedding planes and the rock matrix. Numerical simulations of uniaxial compression tests on slate with varying inclination angles were conducted using the particle flow code PFC-2D. The simulated stress response clearly reflects the mechanical behavior, and the failure modes observed in the models consistently match those from laboratory tests. Based on detailed analysis of stress evolution, the critical boundaries between different failure modes were accurately determined.